1980
DOI: 10.1073/pnas.77.5.2651
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular cloning of Moloney mouse sarcoma virus-specific sequences from uninfected mouse cells.

Abstract: When uninfected mouse cell DNA is cleaved with restriction endonuclease EcoRll, a DNA fragment of 14.0 kilobases can be identified by hybridization to cloned DNA containing sarcoma specific sequences of Moloney mouse sarcoma virus (M-MSVsr). The Murine sarcoma viruses can induce cellular transformation in cultured fibroblasts and fibrosarcomas in animals (1). Moloney murine sarcoma virus (M-MSV) was isolated by passage of Moloney murine leukemia virus (M-MLV) through BALB/c mice (2). The genome of a M-MSV (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 18 publications
(13 reference statements)
3
23
0
Order By: Relevance
“…1 and 3a) are in good agreement with published data on protein and RNA expression (15,31). The absence of detectable hybridization of a vmos-specific probe (oncogene of Moloney murine sarcoma virus; XbaI-HindIII fragment) (26) to any RNA sample served to show that nonspecific hybridization is negligible in the dot-blot technique used in this study (data not shown) (31).…”
supporting
confidence: 80%
“…1 and 3a) are in good agreement with published data on protein and RNA expression (15,31). The absence of detectable hybridization of a vmos-specific probe (oncogene of Moloney murine sarcoma virus; XbaI-HindIII fragment) (26) to any RNA sample served to show that nonspecific hybridization is negligible in the dot-blot technique used in this study (data not shown) (31).…”
supporting
confidence: 80%
“…Filters were hybridised overnight to a DNA probe labelled by random priming with 32P-dCTP (Feinberg & Vogelstein, 1983) at 42°C in 50% formamide, washed at 65°C in 0.1 x standard saline citrate (1 x SSC: 0.15 M NaCl, 0.015 M Na citrate), and 1% sodium dodecyl sulfate (SDS) for 1 h, and exposed to Kodak X-Omat S films (Kodak, Rochester, NY) at -80°C with intensifying screens. The 450bp v-mos probe used in this study was derived by PstI digestion from the pMSV-31 plasmid (Jones et al, 1980).…”
Section: Tumour Inductionmentioning
confidence: 99%
“…3 and in the text, the results of which are shown in lanes A, B, and C, respectively. Lane A contained 10 times less RNA than the other lanes. The nuclease S1 mapping experiments were performed as described (10) Our data show the presence of cis-acting inhibitory sequences 2 kb upstream of c-mos(rat) that act on RNA levels in vivo.…”
mentioning
confidence: 99%
“…Lane A contained 10 times less RNA than the other lanes. The nuclease S1 mapping experiments were performed as described (10) Our data show the presence of cis-acting inhibitory sequences 2 kb upstream of c-mos(rat) that act on RNA levels in vivo. In contrast, the inhibitory sequences found 3' of c-fos(human) appeared to act at the level of translation (14,23).…”
mentioning
confidence: 99%